THE IMPACT OF SUGAR MILLS’ EFFLUENTS ON SOIL QUALITY - S. Ahmad; A. A. Khan (Journal of Animal and Plant Sciences, 2018)
The industrial pollution, like many other developing countries of the world, is the crucial problem of Pakistan. The current study was aimed to ascertain the impact of pollutants added by effluents from sugar mills in Rahim Yar Khan Region of Punjab province in Pakistan.  The electrical conductivity (EC) and pH are the basic parameters to evaluate the soil pollution. To this end, the soil samples were collected from the fixed sites labelled as site I, II, III, IV and V, spaced at fixed distances. Site I was taken as control. From each site the soil samples were taken from the depths ranging between 6 and 48 inches from all the four sugar mills. The samples were examined as per universally used protocols at the regular intervals from May 2007 to April 2008. The results showed the mean highest level of soil ECat Humza Sugar Mills 17.51 dSm-1 (above the standard permissible limits 4.12-8.1 dSm-1) followed by 9.82 dSm-1 at JDW (Jamal Din Wali) Sugar Mills. On the other hand, the highest value of pH 9 was recorded at JDW sugar mills at 24 inches deep soil samples. But the soil samples collected from 6-18 inches sediments showed the pH ranging between 8.7 at United Sugar Mills and 10.9 at Ettehad Sugar Mills. The findings established that two out of four sugar mills were adding pollutants to the crops cultivation fields via canal water that was being contaminated primarily by effluents. It was hypothesized that the sugar mills in the study area might be engaged in polluting the habitats in their vicinity.
Keywords: Sugar Mills; Pollution; Soil Electrical Conductivity (EC); Soil pH